Contact zone of two different chloroplast lineages and genetic guidelines for seed transfer in Quercus serrata and Quercus crispula. Issue 1 (12th October 2020) - Onosato, Kataru; Shitara, Takuto; Matsumoto, Asako; Matsuo, Ayumi; Suyama, Yoshihisa; Tsumura, Yoshihiko
Abstract: Within their natural distribution ranges, plant species exhibit a genetic structure that has been created by global climate change and natural selection over long periods. This genetic structure needs to be conserved for sustainable use of genetic resources. To conserve local forests with different genetic structures, genetic guidelines for seed and seedling transfer in individual species are necessary. Genetic guidelines have been published for 43 Japanese tree species using population genetic data; however, for practical use, more detailed genetic borders between important genetic lineages should be clarified to inform seed collection and planting. Thus, we investigated in detail the genetic borders between two important Japanese oak species, Quercus serrata and Quercus crispula, in the Chubu region of Japan using chloroplast and nuclear DNA markers, and we discuss the factors that influenced border creation using the results of species distribution modeling (SDM). The chloroplast DNA (cpDNA) haplotype was clearly different within the Chubu region of Japan but the difference in nuclear DNA between northern and southern haplotype populations was very small, both in Q. serrata and Q. crispula . The results of SDM showed that during the last glacial maximum (LGM) Q. serrata was distributed mostly along the coastline but Q. crispula was distributed not only along the coast but also in mountainous areas further inland. The cpDNA genetic borders of these two oak species are complex and seem to have been influenced by topography and their distribution during the LGM. We propose and discuss genetic guidelines for these two oak species based on the results of this study. Abstract : We investigated in detail the genetic borders between two important Japanese oak species, Quercus serrata and Quercus crispula, in the Chubu region of Japan using chloroplast and nuclear DNA markers, and we discuss the factors that influenced border creation using the results of species distribution modeling (SDM). The chloroplast DNA (cpDNA) genetic borders of these two oak species are complex and seem to have been influenced by topography and their distribution during the LGM.